Study on body composition and its correlation with obesity: A Cohort Study in 5121 Chinese Han participants. Issue 21 (May 2018) - Liang, Xiongfei; Chen, Xianhua; Li, Jing; Yan, Mengdan; Yang, Yifeng
Abstract : Abstract: Rare reports can be found about sex- and age-specific body composition survey among Chinese population. The aim of this study is to explore the change of body composition with aging in Chinese males and females respectively. The present cross-sectional study was carried out in Central South University Xiangya School of Medicine Affiliate Haikou Hospital, on a random sample consisting of 5121 participants. Inbody720 body composition analyzer was used to detect the human body composition. Data collection was based on the assessment of anthropometric body composition measurements done with the help of bioelectric impedance. And the data were analyzed with SPSS19.0. We selected 5121 participants, 3276 males and 1845 females. A significant trend ( P < 0 .05) for all anthropometric indices was observed with age for both genders. Body fat in men and women were 18.33 kg and 19.82 kg, respectively. Body fat percentage in men and women were 25.74% and 34.01%, respectively. Visceral fat area in men and women were 91.98 cm 2 and 77 cm 2, respectively And, with the increase of age, body fat, body fat percentages and visceral fat area also increased, both in men and in women. Meanwhile, with the increase of BMI, the body fat, body fat percentages, and visceral fat area also increased, both in men and in women. Significant trends were observed for body fat, body fat percentages and visceral fat area for both genders with age and both genders with BMI. Focusing on obesity-related lifestyle and prevent weight gain.